Unmet Need for Family Planning in Nepal during the First Two Years Postpartum. (5th June 2014) - Mehata, Suresh; Paudel, Yuba Raj; Mehta, Ranju; Dariang, Maureen; Poudel, Pradeep; Barnett, Sarah
Abstract : Contraceptive use during the postpartum period is critical for maternal and child health. However, little is known about the use of family planning and the determinants in Nepal during this period. This study explored pregnancy spacing, unmet need, family planning use, and fertility behaviour among postpartum women in Nepal using child level data from the Nepal Demographic and Health Surveys 2011. More than one-quarter of women who gave birth in the last five years became pregnant within 24 months of giving birth and 52% had an unmet need for family planning within 24 months postpartum. Significantly higher rates of unmet need were found among rural and hill residents, the poorest quintile, and Muslims. Despite wanting to space or limit pregnancies, nonuse of modern family planning methods by women and returned fertility increased the risk of unintended pregnancy. High unmet need for family planning in Nepal, especially in high risk groups, indicates the need for more equitable and higher quality postpartum family planning services, including availability of range of methods and counselling which will help to further reduce maternal, perinatal, and neonatal morbidity and mortality in Nepal.